Experimental benchmark data for Monte Carlo simulated radiation effects of gold nanoparticles. Part II: comparison of measured and simulated electron spectra from gold nanofoils. (1st May 2023) - Borbinha, Jorge; de la Fuente Rosales, Liset; Hepperle, Philine; Nettelbeck, Heidi; Baek, Woon Yong; Di Maria, Salvatore; Rabus, Hans
Abstract: Electron emission spectra of a thin gold foil after photon interaction were measured over the energy range between 50 eV and 9500 eV to provide reference data for Monte Carlo radiation-transport simulations. Experiments were performed with the HAXPES spectrometer at the PETRA III high-brilliance beamline P22 at DESY (Hamburg, Germany) for photon energies just below and above each of the gold L-edges, that is, at 11.9 keV, 12.0 keV, 13.7 keV, 13.8 keV, 14.3 keV, and 14.4 keV. The data were analyzed to obtain the absolute values of the particle radiance of the emitted electrons per incident photon flux. Simulations of the experiment were performed using the Penelope and Geant4 Monte Carlo radiation-transport codes. Comparison of the measured and simulated results shows good qualitative agreement. On an absolute scale, the experiments tend to produce higher electron radiance values at the lower photon energies studied as well as at the higher photon energies for electron energies below the energy of the Au L3 photoelectron. This is attributed to the linear polarization of the photon beam in the experiments, something which is not considered in the simulation codes.